New thiocyanate-free ruthenium(ii) sensitizers with different pyrid-2-yl tetrazolate ligands for dye-sensitized solar cells1. Issue 26 (14th July 2015) - Colombo, Alessia; Dragonetti, Claudia; Magni, Mirko; Meroni, Daniela; Ugo, Renato; Marotta, Gabriele; Grazia Lobello, Maria; Salvatori, Paolo; De Angelis, Filippo
<x xml:space="preserve">Abstract</x> The synthesis of two new stable thiocyanate free Ru(ii) complexes with different pyrid-2-yl tetrazolate ligands is reported, along with promising DSSCs.